Perception of Tertiary Students on Code-Switching Advertisement - Rosmawaty Harahap (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2023)
This study aimed to look at the effects of code-switching in advertising. Descriptive-analytic research was used to ascertain how Indonesian tertiary students see code-switched internet advertising. Data from university students (N = 100) in Indonesia were gathered using a questionnaire as the study's tool. Once the data had been collected, it was computerised, and the descriptive statistics (frequency and percentage) were used to tabulate it. According to the research, most tertiary students in Indonesia believed that code-switched online advertisements had a more significant influence than monolingual advertisements. Since the code-switched commercial was original, appealing, not confusing, easily intelligible, and didn't obliterate the Indonesian language, it has stayed in their minds and had a favourable impact. Additionally, most respondents concurred that code-switched internet adverts persuaded them to purchase the supplied goods. As a result, code-switched advertising favours Indonesia's online business environment since it is a very innovative, effective, and helpful method for developing marketing expertise.